Nuts & seeds in health and disease prevention - Patel, Vinood B.; Preedy, Victor R.; Watson, Ronald R. [ (Ronald Ross)] (Academic Press, 2011)
The use of nuts and seeds to improve Human nutritional status has proven successful for a variety of conditions including in the treatment of high cholesterol, reduced risk of Type-2 Diabetes, and weight control. This guide to the health benefits of nuts and seeds explores the specific factors that contribute to these potential health benefits